2010
DOI: 10.3109/08860220903367544
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Expression of Perlecan in the Aorta of Secondary Hyperparathyroidism Model Rats with Medial Calcification

Abstract: It may be that reduced expression of perlecan in the calcified aortae of hyperparathyroid rats is a risk factor for vascular calcification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 33 publications
3
19
0
Order By: Relevance
“…Consistent with this idea, proteoglycans and HS can function as potent inhibitors of hydroxyapatite formation [24, 25]. Interestingly, reduced levels of Pln also were found to be associated with vascular calcification of smooth muscle cells in the aorta of an experimental rat model [26], suggesting that Pln interaction with factors that promote calcification can protect various tissue types from pathological mineralization. Furthermore, recent data consistent with this study showed that Pln deficiency is associated with a decrease in osteocytes’ pericellular space which suggested that Pln and its HS chains prevent tissue mineralization [17].…”
Section: Discussionmentioning
confidence: 88%
“…Consistent with this idea, proteoglycans and HS can function as potent inhibitors of hydroxyapatite formation [24, 25]. Interestingly, reduced levels of Pln also were found to be associated with vascular calcification of smooth muscle cells in the aorta of an experimental rat model [26], suggesting that Pln interaction with factors that promote calcification can protect various tissue types from pathological mineralization. Furthermore, recent data consistent with this study showed that Pln deficiency is associated with a decrease in osteocytes’ pericellular space which suggested that Pln and its HS chains prevent tissue mineralization [17].…”
Section: Discussionmentioning
confidence: 88%
“…Standard curves for rHspg2 and rGAPDH exhibited similar slopes, allowing GAPDH‐normalized gene expression levels to be determined using the ΔΔCt method. Primers sets included rGAPDH: Forward, CCAGC CTCGTCTCATAG; Reverse, ACTTGCCGTGGGTAG AGTC, and rHspg2: Forward, CCCTGGCAACAGCTTCTCTA; Reverse, ATGGCCATCCTGTAGTCCAA. All assays were run in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…3.2.1. Low Molecular Weight Substances, Increased in Blood in CKD (Table 1) A high ambient phosphate concentration triggers calcification in a variety of situations, as shown in vitro in human VSMC [29,30,[32][33][34], rat and mouse VSMC [35,36], rat aortic rings [33], as well as in aortas of rats subjected to 5/6 nephrectomy [35]. Apo −/− mice with 5/6 nephrectomy displayed aortic valve calcification 12 weeks after surgery both when fed a high phosphate diet as well as a control diet, though with increased calcium deposits detected upon high phosphate diet [36].…”
Section: Effect Of the Identified Substances On Cardiovascular Calcifmentioning
confidence: 99%
“…The calcium-phosphate metabolism is one of the key factors for initiation and progression of vascular calcification in CKD [60] and in vitro as well as ex vivo studies showed increased calcification upon increased levels of calcium [38,40] or inorganic phosphate [29,32,33,35]. In late stage CKD (CKD 4-5), most of CKD patients present with hyperphosphatemia [61,62].…”
Section: Mechanisms and Signalling Pathways Associating Uremic Toxinsmentioning
confidence: 99%